Examining the Factors That Influence Students’ Participation in Class Room Dialogue and their Learning Outcomes: An Empirical Study - Tyagi , Nishi; Srivastava, Akanksha (International Journal of Psychosocial Rehabilitation, 2020)
–Education plays an important role for everyone to succeed in life and get something different. It helps a lot in lessening the challenges of life or difficulties of life. Knowledge gained throughout the education period enables every individual to be confident about their life. Transfer of Knowledge has always been the accepted norm of teaching and learning in the traditions of the schooling system in rural India since ancient times. The ’Gurukul’ system of teaching converted to the missionary schools’ format during and post the British rule in India. This concomitant of two cultures has had a debilitating impact on the overall teaching in itself. This has been further impacted upon by the onslaught of Information Communication Technology (ICT) which has revolutionized the learning at lightning speed. Due to this, the rural schooling system in India has been finding itself at the darker end of the tunnel. The objective of the research is to find the aspects of opening a healthy dialogue between students and teachers, especially in the rural setting to make the vital step towards fostering world-class learning and teaching. The sample of study were the schools in a rural area of Bilaspur District, Himachal Pradesh, Northern India with emphasis on Government schools. The methodology adopted was the conduction of focused group discussion among teachers and principals of rural government schools. The outcomes of the discussions are the sample drawn upon for the study findings. The study findings show that most teachers have been experimenting with the promotion of interactive dialogue methods in the classroom setting but have not met with little success as several socio-economic and socio-psychological parameters need to be addressed/ considered before attaining any success in this research